1983
DOI: 10.1007/bf00251814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on human erythrocyte membrane fluidity in diabetes mellitus

Abstract: Summary. The effect of insulin in vitro on the fluidity of the human erythrocyte membrane in Type I (insulin-dependent) diabetic patients and healthy control subjects was investigated using a fluorescence technique. It was found that the addition of 10 -9 mol/1 porcine insulin significantly increased fluorescent probe lateral mobility in the membrane lipid layer but did not appear to produce any conformational changes of membrane proteins.Key words: Insulin, erythrocyte membrane, lateral mobility,Interest in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Plasma membrane of hepatocytes from streptozocin-diabetic rats have been shown to have low fluorescence polarization values, suggesting an increase in membrane fluidity with the DPH probe [21]. Bryszewska and Leyko [9] demonstrated increased membrane viscosity by using a different technique, measuring the lateral mobility of a lipophilic probe (pyrene). Bryszewska et al [22] found a higher membrane cholesterol/phospholipid ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma membrane of hepatocytes from streptozocin-diabetic rats have been shown to have low fluorescence polarization values, suggesting an increase in membrane fluidity with the DPH probe [21]. Bryszewska and Leyko [9] demonstrated increased membrane viscosity by using a different technique, measuring the lateral mobility of a lipophilic probe (pyrene). Bryszewska et al [22] found a higher membrane cholesterol/phospholipid ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications in the erythrocyte membrane could be the cause of these theological abnormalities. Biochemical abnormalities have been described [5][6][7] in the membrane, and change in its viscosity have been demonstrated by the fluorescence polarization technique [7][8][9] or electron spin resonance [10]. However, these results have been challenged [11].…”
mentioning
confidence: 89%
“…It is clear that various physical properties of the erythrocyte membrane, such as deformability [24], doublet formation [25] and microviscosity [26] may be altered in poorly controlled diabetes. There is, however, no evidence which directly links nonenzymatic glycosylation with these abnormalities, and other factors such as pH, changes in the lipid composition of the membrane [27], lipid-protein interactions [28] or a direct insulin effect [29] may be important.…”
Section: Erythrocyte Proteinsmentioning
confidence: 99%
“…The relative increase of polyunsaturated acids (PUFA; mainly 20:4 and/or 22:6) found by the three groups mentioned seems in contradiction to others (11,12). In T1DM, the unifying mechanism behind all of these changes has been postulated to be the deficiency in insulin because it has been observed that insulin treatment, which is known to improve membrane fluidity (4,5) and blood viscosity (13), also increases conversion of dietary (n-6) fatty acids (mainly linoleic acid, 18:2) to PUFA (mainly arachidonic acid, 20:4) (14).…”
mentioning
confidence: 67%
“…The increased blood viscosity seen in diabetes (1) and more so in patients with established complications (2) has been ascribed to a decrease in erythrocyte deformability (3) and to changes in erythrocyte membrane fluidity (4,5). The extent to which these changes are due solely to alterations in the lipid composition of the erythrocyte membrane is still controversial.…”
mentioning
confidence: 99%